CHARACTER BUILDING THROUGH SOCIAL SCIENCE LEARNING IN ELEMENTARY SCHOOLS - Wildan Nuril Ahmad Fauzi (Sunan Kalijaga International Journal on Islamic Educational Research, 2020)
Ips learning has a role to play in fostering citizens in building the character of the nation. Character is a set of values that have become a habit of life so that it becomes a fixed trait in a person. this method of writing uses library research using a philosophical approach (reviewing children's education policy from a family perspective). Data collection techniques used in articles are documentation techniques that collect data material in the form of sources of books in the library, articles related to writings related to research, and collected and collected and insticronized and associated with the object of study. Research results In an effort to character-building learners in schools through social studies learning at least includes 4 things that must be done, namely curriculum, materials, teachers, and learning process. The curriculum in schools must be able to develop knowledge, skills, attitudes, values, and morals. Ips material is prepared and designed to introduce concepts related to people's lives and develop knowledge, understanding, and ability to social conditions in society.